Behavioural adaptation of Malay families and housing modification of terrace houses in Malaysia / Zaiton Abdul Rahim and Ahmad Hariza Hashim - Hashim, Ahmad Hariza (Faculty of Architecture, Planning and Surveying, 2013)
This paper examines the behavioural adaptation of Malay families living in terrace houses with regards to the activity system, privacy and social interaction among Malay families and terrace housing modification.